Perbandingan Metode Forward Chaining dan Backward Chaining Dalam Mendiagnosis Perkembangan Anak Usia Dini - Sofyana Ibrahim; Debby Paseru; Vivie Deyby Kumenap (Ikatan Ahli Informatika Indonesia, 2021)
Development in humans occurs from birth to adulthood, therefore parents have a very important role in paying attention to the development of children. The survey conducted by the author shows that not all parents will see a doctor to check their child's growth and development because they are busy working and will only go to the doctor when their child is in an unhealthy condition. From the survey data in the form of questionnaires collected, some parents also do not know what symptoms affect their child's growth and development. If a child has a developmental disorder and parents rarely consult to find out how high the level of the disorder is, it will worsen the growth and development of the child so that the number of developmental disorders in children will increase. Based on the problems above, an Early Childhood Development Expert System application was built using the Forward Chaining Method and the Backward Chaining Method, the reason for using both methods is to be different from previous research and the search process can be more varied. The forward chaining method looks for disorders based on the symptoms selected by the user. The backward chaining method is used to determine the level of disorders that occur in children based on the symptoms and disorders selected by the user. The application is built using the PHP programming language and the Unified Modeling Language (UML) modeling tool. The results of the implementation of this scientific work are able to produce an early childhood development expert system application that can detect symptoms or disorders using the Forward Chaining and Backward Chaining methods. This application is ready and suitable for users to detect symptoms or disorders.